2015
DOI: 10.1159/000377629
|View full text |Cite
|
Sign up to set email alerts
|

Activated Platelets Induce Estrogen Receptor β Expression in Endometriotic Stromal Cells

Abstract: Background/Aims: Endometriosis is viewed first and foremost as an estrogen-dependent disease, featuring not only excessive estrogen production but also aberrant expression of estrogen receptors (ERs), particularly ERβ, that mediate the estrogen action. ERβ is the predominant ER in mediating estrogen action in endometriosis, and estrogen plays a vital role in the development of endometriosis; thus, ERβ is viewed as a strong candidate for therapeutic targeting. Given our recent finding that platelets aggregate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 33 publications
(45 reference statements)
5
26
0
1
Order By: Relevance
“…In vitro, PRP upregulated the gene expression of ERalpha, ERbeta, and the progesterone receptor in cultured bovine endometrial cells [65], leading the authors to suggest that intrauterine infusion of PRP in cattle may improve their fertility [65,73]. Activated platelets also induced ERbeta (the predominant ER in mediating estrogen action in endometriosis), mRNA, and protein expression in endometriotic stromal cells from ovarian endometrioma [74]. In our study, we did not observe differential expression of estrogen or progesterone receptor transcripts in response to PRP or PPP treatment likely due to species differences and different source of human cells used compared to above studies.…”
Section: Prp Effect Of Sex Hormone Receptor Expressionmentioning
confidence: 99%
“…In vitro, PRP upregulated the gene expression of ERalpha, ERbeta, and the progesterone receptor in cultured bovine endometrial cells [65], leading the authors to suggest that intrauterine infusion of PRP in cattle may improve their fertility [65,73]. Activated platelets also induced ERbeta (the predominant ER in mediating estrogen action in endometriosis), mRNA, and protein expression in endometriotic stromal cells from ovarian endometrioma [74]. In our study, we did not observe differential expression of estrogen or progesterone receptor transcripts in response to PRP or PPP treatment likely due to species differences and different source of human cells used compared to above studies.…”
Section: Prp Effect Of Sex Hormone Receptor Expressionmentioning
confidence: 99%
“…Indeed, it has recently been shown that platelets can promote angiogenesis and cellular proliferation (Ding et al, 2015), and platelet depletion and the treatment with a recombinant P-selectin can effectively reduce lesion area in murine models of endometriosis (Ding et al, 2015;Guo et al, 2015a). Platelets also induce the expression of oestrogen receptor β (ERβ) in endometriotic stromal cells (Zhang et al, 2015), which has shown recently to modulate apoptosis complexes and the inflammasome to drive the pathogenesis of endometriosis (Han et al, 2015). Consistent with the role of platelets in endometriosis, it has recently been reported that women with endometriosis are in a hypercoagulable state, featuring elevated platelet activation in their peripheral blood (Wu et al, 2015).…”
mentioning
confidence: 99%
“…And this may explain as why ERβ, but not ERα, is overexpressed in endometriosis 35,36 . Incidentally or not, we have shown previously that ERβ expression can also be upregulated by activated platelets 73 .…”
Section: Discussionmentioning
confidence: 87%
“…cell culture and reagents. Endometriosis-derived primary human endometriotic stromal cells (HESCs) were isolated and cultured as reported previously 23,73 . Briefly, the endometriotic tissues were minced into small pieces of about 1 mm³ in size, after washing with DMEM/F-12 medium (Dulbecco's modified Eagle's medium/ Ham's F-12 medium, Hyclon, Logan, UT, USA) supplemented with 100 IU/mL penicillin and 100 mg/ml streptomycin (Invitrogen, Paisley, UK).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation